2014
DOI: 10.1038/gim.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oncogenetics training on general practitioners’ consultation skills: a randomized controlled trial

Abstract: Purpose:General practitioners are increasingly called upon to deliver genetic services and could play a key role in translating potentially life-saving advancements in oncogenetic technologies to patient care. If general practitioners are to make an effective contribution in this area, their genetics competencies need to be upgraded. The aim of this study was to investigate whether oncogenetics training for general practitioners improves their genetic consultation skills.Methods:In this pragmatic, blinded, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 39 publications
0
58
0
4
Order By: Relevance
“…Third, although near all studies indicated that their training programs successfully increased participants' knowledge, attitudes, skills, intention, self-efficacy, comfort level, and/or practice behavior in genomics practice, a few studies adopted rigorous study designs and evaluation plans. In fact, only 7 of the 44 reviewed articles 6,24,34,37,39,43,45 used a quasi-experimental design or randomized controlled trial/experimental design. The majority of the studies did not collect follow-up data, utilize advanced statistical techniques to control potential confounders, or report data validity and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although near all studies indicated that their training programs successfully increased participants' knowledge, attitudes, skills, intention, self-efficacy, comfort level, and/or practice behavior in genomics practice, a few studies adopted rigorous study designs and evaluation plans. In fact, only 7 of the 44 reviewed articles 6,24,34,37,39,43,45 used a quasi-experimental design or randomized controlled trial/experimental design. The majority of the studies did not collect follow-up data, utilize advanced statistical techniques to control potential confounders, or report data validity and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding in our study about decreased provider knowledge and recall about PGx testing following the intervention period may also be attributed to physicians' reliance on the pharmacist. Development of a longer CME or a series of CME sessions might have proven more effective to promote provider's knowledge as has been demonstrated elsewhere [38], and could have potentially reduced the need for a pharmacist for an extended period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Seven papers investigated educational interventions for clinicians, including six evaluations of novel education interventions 11,29,[47][48][49][50] and one systematic review. 51 The studies reported that education interventions improved genetics knowledge amongst clinicians.…”
Section: Genomics/genetics Educationmentioning
confidence: 99%